2016
DOI: 10.1038/ncomms11770
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic protein coronas revealed as a modulator of silver nanoparticle sulphidation in vitro

Abstract: Proteins adsorbing at nanoparticles have been proposed as critical toxicity mediators and are included in ongoing efforts to develop predictive tools for safety assessment. Strongly attached proteins can be isolated, identified and correlated to changes in nanoparticle state, cellular association or toxicity. Weakly attached, rapidly exchanging proteins are also present at nanoparticles, but are difficult to isolate and have hardly been examined. Here we study rapidly exchanging proteins and show for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
81
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 68 publications
3
81
0
4
Order By: Relevance
“…There was a relatively mild transient degree of inflammatory response with little evidence of an oxidative stress or protein exudation, but associated with an acute release of cytokines. The mild inflammatory response may be linked to the dissolution and transformation of the surface of the AgNWs to Ag 2 S seen intracellularly, here in ATII cells, and also inside J774 macrophage cells in vitro , 16 and hence their inactivation leads to a reduced dissolution rate of the nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a relatively mild transient degree of inflammatory response with little evidence of an oxidative stress or protein exudation, but associated with an acute release of cytokines. The mild inflammatory response may be linked to the dissolution and transformation of the surface of the AgNWs to Ag 2 S seen intracellularly, here in ATII cells, and also inside J774 macrophage cells in vitro , 16 and hence their inactivation leads to a reduced dissolution rate of the nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…18 This process of NP sulfidation has also been observed when AgNPs were incubated with a J774 macrophage cell line in vitro. (16) We suggested that sulfidation occurred through the action of sulfide species, including H 2 S, HS – , or S 2– , which are present inside human lung tissues. Since no evidence of cytotoxicity was observed, we proposed that the precipitation of Ag + ions released from the AgNWs as highly insoluble Ag 2 S may act as a detoxification mechanism that could limit their short-term toxicological effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coating or functionalising silver NPs’ surfaces with polymers or biomolecules, including proteins, alters the silver NPs’ size and properties due to the formation of a coronal structure formed upon subsequent contact with biological fluids from host tissues. 3,30,33,36,51 Hard and soft coronal structures and compositions alter the silver NP structure and size and therefore can affect both their innate antimicrobial properties and cellular cytotoxicity. 33,35 The effects of the transient, soft corona layer on silver NP function and cellular uptake have not yet been studied in detail due to the inability to distinguish accurately the rapidly exchanging, weakly bound proteins in various biological environments.…”
Section: Introductionmentioning
confidence: 99%
“…33,35 The effects of the transient, soft corona layer on silver NP function and cellular uptake have not yet been studied in detail due to the inability to distinguish accurately the rapidly exchanging, weakly bound proteins in various biological environments. 51 However, the sustained complex protein corona properties have been linked to NP aggregation and cellular association. 36,51 Agglomeration substantially reduces the antimicrobial capacity of silver NPs, so maintaining a dispersed and stable silver NP population is critical.…”
Section: Introductionmentioning
confidence: 99%